Perivascular extension of microwave ablation zone: demonstrated using an ex vivo porcine perfusion liver model*. (3rd October 2018) - Singh, Saurabh; Siriwardana, Pulathis Nilantha; Johnston, Edward William; Watkins, Jennifer; Bandula, Steven; Illing, Rowland; Davidson, Brian Ritchie
Abstract: Microwave ablation (MWA) has been proposed to suffer less from the heat sink effect compared to radiofrequency ablation but has been reported to cause extension of the ablation zone along intrahepatic vessels in clinical practice. To study this effect in detail, eight fresh porcine livers were perfused in an ex vivo organ perfusion system. Livers were perfused with oxygenated, O-positive human blood at 37 °C. Perfusion was discontinued immediately before ablation in the non-perfused group ( n  = 4) whilst in the perfused group ( n  = 4) perfusion was maintained during MWA (140 W X 2 min). Large intrahepatic vessels (> 6 mm) were avoided using ultrasound. MWA zones were bisected within 30 min of perfusion termination and sections were fixed in formalin and stained with H&E and NADH to assess cell viability. Magnetic resonance imaging (MRI) was performed on two livers (one perfused, one non-perfused) to provide imaging correlation before sectioning. Twenty-one out of a total of 30 MW ablation zones (70%) showed extension of the ablation zone along a vessel. There was no statistically significant difference ( p  = 1) in the incidence of ablation zone extension between perfused (9/13, 69%) and non-perfused organs (12/17, 71%). MRI also demonstrated ablation zone extension along blood vessels correlating with macroscopy in two livers. NADH staining also confirmed extension of the ablation zone. Liver MWA appears to be commonly associated with propagated thermal injury along adjacent vessels and occurs independent of active blood flow. In order to avoid possible complications through non-target tissue injury, this effect requires further investigation.